Caracterização de perfis longitudinais dos rios nas bacias hidrográficas do Paraná III (Brasil) e Alto Paraná (Paraguai) - Baller, Lindomar (2014)
The paper presents the morphometric characteristics of the drainage channels, listing discussions regarding longitudinal profiles. The purpose of this research is to address the characteristics of longitudinal profiles of rivers in the basin of Paraná III (Western Paraná State, Brazil) and Alto Paraná (East Paraguay). The surveys were conducted in 19 sub-basins, being drafted in the longitudinal profiles of 11 major rivers in the Paraná III in 8 channels and rivers in the Alto Paraná basin. The rivers of both basins flow into the Itaipu lake (220 m above sea level). Longitudinal profiles were compiled from the altimetric information obtained on topographical maps (1:50,000 scale) for the Paraná III basin and SRTM (30 m) for the Alto Paraná basin, with the help of the Global Mapper software (13.0), the from the contours with contour interval of 20 meters. The longitudinal profiles describe the altimetric differences of channels (slope m/m), thus characterizing the longitudinal anomalies (knickzones). Detected a higher slope in the rivers belonging to the Paraná III (Brazil). In this basin, the greatest source of altimetry in the channel identified in the river Santa Quitéria, which lies at an altitude of 764 m. Other six channels of the Paraná III have quotas in excess of 550 m altitude spring. The other channels have lower source levels at 440 m, with the smallest headspring of river Passo-cue, to 305 m above sea level, located at the southern end of the Paraná III. The highest elevation in the source of the rivers of the Alto Paraná basin (Paraguay) basin is 440 m in Carapa River, with other channels featuring near this value dimensions, ranging up to a minimum quota of 280 m at the source of river Pira Pyta, also the south end of the basin. These data indicate altimetric difference between both basin, with higher elevation relief in the Paraná III in relation to the Alto Paraná basin. Due to its higher slope also has a higher number of reach with slope ruptures, 25 knickzones being identified. In the Alto Paraná basin was identified only 8 knickzones. The spatial distribution of abrupt breaks identified a higher frequency of knickzones in two geomorphic units in the Paraná III basin: San Francisco and Cascavel with 14 and 9 knickzones respectively. Theses geomorphic units show a strong to intermediate degree of dissection